Hydrophobic associated copolymer as a wide temperature range synthetic cement retarder and its effect on cement hydration. Issue 35 (11th May 2017) - Xia, Xiujian; Guo, Jintang; Chen, Di; Feng, Yakai; Yu, Yongjin; Jin, Jianzhou; Liu, Shuoqiong
ABSTRACT: Hexadecyldimethylpropylmethacrylamide ammonium bromide was well prepared, allowed to copolymerize with other functional monomers to develop a hydrophobic associated polymer (PIADH) as a wide temperature range cement retarder. The synthetic copolymer was testified by Fourier transform infrared spectroscopy, 1 H‐nuclear magnetic resonance, thermo gravimetric analysis, and differential scanning calorimetry. Its temperature induced adaptability was verified via fluorescence probe and NaOH titration techniques, indicating that the retarding groups were increasing at elevated temperature. The applied performance of PIADH modified cement slurries was also evaluated. The results manifested that PIADH not only had excellent retarding property, but also was insensitive to its concentration and temperature variations. Meanwhile, it exhibited less impact on the compressive strength of set cement in large temperature difference. Besides, the inclusion of PIADH improved the microstructure of hardened cement, which was conducive to its mechanical property. The effect of PIADH on cement hydration was also investigated by the isothermal heat flow calorimetry and X‐ray diffraction, showing that the retardation of PIADH was achieved through prolonging the induction period and inhibiting the nucleation of portlandite and ettringite crystals. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45242. Abstract :